Redescription of the Central American genus Moribaetis Waltz & McCafferty 1985 (Ephemeroptera, Baetidae) - Kluge, Nikita J.; Vega, Juan A. Bernal (Zootaxa, 2018)
A new definition for the genus Moribaetis Waltz & McCafferty 1985 is given. Its type species, Moribaetis maculipennis (Flowers 1979) is redescribed based on male and female imagoes reared from larvae near the type locality in Panama. Larvae, formerly wrongly attributed to Moribaetis salvini (Eaton 1885), and a male imago, formerly wrongly attributed to Moribaetis macaferti Waltz 1985, belong to a new species Moribaetis latipennis sp. n., which is described here based on a male imago reared from larva in Panama. Both species, M. maculipennis and M. latipennis sp. n., are distinct from M. salvini, which is known as a single male imago (lectotype) from Costa Rica. All other species, formerly attributed to Moribaetis, are excluded from this genus; a new combination Caribaetis macaferti comb. n. is proposed for the species originally described as Moribaetis macaferti Waltz (in Waltz & McCafferty) 1985, and a new combination Baetis (Rhodobaetis) mimbresaurus comb. n. is proposed for the species originally described as Moribaetis mimbresaurus McCafferty 2007.